Pengaruh Beberapa Khamir Antagonis terhadap Penyakit Antraknosa dan Umur Simpan pada Buah Mangga - Riana Jumawati; Roedhy Poerwanto; Suryo Wiyono; Ketty Suketi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Effect of Various Yeasts Antagonists on Anthracnose Disease and the Shelf Life of MangoPostharvest decay on mango may occur due to physiological damage and/or postharvest disease especially anthracnose. This postharvest decay may decrease the quality of mango fruit. The use of antagonists yeast as biocontrol agent is an alternative control measure for postharvest diseases of fruits. This study aimed to screen yeast species as biological control agents and in the same time delaying the maturity of fruits to extend its shelf life. Six isolates of yeasts were evaluated, namely Cryptococcus albidus, Cryptococcus terreus, Aureobasidium pullulans, Rhodotorula minuta, Candida tropicalis, Pseoudozyma hubeiensis); fungicides treatment using azoksistrobin was applied for comparative treatment. The study was conducted at two temperature conditions, namely room temperature and 15 ° C. It was evidenced that C. albidus, A. pullulans, and C. tropicalis were effective to control anthracnose disease on mango under both temperatures. Furthermore, C. tropicalis and A. pullulans were able to extend manggo shelf life for 21 days at room temperature and for 54 days at 15 °C, respectively.